2017
DOI: 10.1080/14397595.2017.1404711
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-inducible Mx1 protein is highly expressed in renal tissues from treatment-naïve lupus nephritis, but not in those under immunosuppressive treatment

Abstract: Mx1 levels were upregulated in lupus peripheral blood even when their disease activities were stable. On the other hand, Mx1 was highly expressed in kidneys from patients with LN before treatment, which was decreased after immunosuppressive treatment. These results suggest that Mx1 is a potential marker for the diagnosis of SLE in the peripheral blood and also for the activity of lupus nephritis in the kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…MX1 is downstream in the type I IFN pathway and is an important component of the early innate immune system, as it plays a role in the IFN-induced antiviral response against various viruses, but its role in response to IFN stimulation in the absence of virus has yet to be determined (39)(40)(41). MX1 hypomethylation, increased RNA expression, and higher protein concentrations are consistently observed in SLE patients (20,(42)(43)(44). Multiple CpGs associated with MX1 were observed to be highly associated with SLE status in this analysis, and methylation at 2 MX1 CpGs revealed almost perfect separation of AA patients with SLE from controls, leading us to hypothesize that a targeted assay for MX1 methylation would be fruitful in diagnosing SLE.…”
Section: Discussionmentioning
confidence: 99%
“…MX1 is downstream in the type I IFN pathway and is an important component of the early innate immune system, as it plays a role in the IFN-induced antiviral response against various viruses, but its role in response to IFN stimulation in the absence of virus has yet to be determined (39)(40)(41). MX1 hypomethylation, increased RNA expression, and higher protein concentrations are consistently observed in SLE patients (20,(42)(43)(44). Multiple CpGs associated with MX1 were observed to be highly associated with SLE status in this analysis, and methylation at 2 MX1 CpGs revealed almost perfect separation of AA patients with SLE from controls, leading us to hypothesize that a targeted assay for MX1 methylation would be fruitful in diagnosing SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney biopsies of patients with SLE show increased expression of IFN-inducible genes108–110 and pDCs accumulate in glomeruli of patients with active disease 50. A stronger IFN signature is observed in glomeruli and renal tubule in patients with immunosuppressive naïve SLE with nephritis compared with patients with SLE nephritis having received immunosuppressive treatment 111. In kidney tissue, IFN-β can induce podocyte cell death and increase permeability whereas both IFN-α and IFN-β suppress renal progenitor cell differentiation into mature podocytes,112 resulting in podocyte loss, proteinuria and impaired glomerular repair.…”
Section: Introductionmentioning
confidence: 99%
“…Another hub gene interferon-induced is MX1. It has been reported that this molecule is highly expressed during renal disease like lupus nephritis, and that this could be possible to cause kidney inflammation [87]. Moreover, another study supports this gene behavior.…”
Section: Interactome Analysis and Hub Genes Identificationmentioning
confidence: 59%